Estrutura da comunidade de morcegos (Mammalia, Chiroptera) da Estação Experimental de Itirapina, estado de São Paulo, Brasil - Sato, Therys M.; Carvalho-Ricardo, Maria Carolina de; Uieda, Wilson; Passos, Fernando C. (Papéis Avulsos de Zoologia, 2015)
The structure of Brazilian bat communities is poor studied and they have been modified due to the loss of part of their habitats. Here we studied bat community in Estação Experimental de Itirapina, state of São Paulo, Southeastern Brazil. In addition to the cultivated species of Eucalyptus and Pinus in this place, native and exotic plants supply food to the bats. Four to twelve mist nets were opened in 58 nights, from July 2001 to July 2006. A total of 720 individuals of 16 bat species were caught: Five species (Artibeus lituratus, Platyrrhinus lineatus, Carollia perspicillata and Sturnira lilium) accounted for 80% of the captures. All of them are abundant in disturbed areas and feed on pioneer species, such as Cecropia pachystachya, Solanum spp. and Piper spp. Estação Experimental de Itirapina is an important place for supplying roosting and food sources for bats.